Tax savvy for small business 2025 - Secor, Glen (Nolo, 2025)
This completely updated edition covers changes in tax rates, deductions, and credits. The 23rd edition also identifies important small business tax benefits that are scheduled to expire after 2025. Tax Savvy for Small Business is the up-to-date resource you need to maximize your deductions and boost your business's bottom line.